Integrasi Rantai Nilai, Kelembagaan, dan Kebijakan dalam Sistem Agribisnis Bunga Telang di Kabupaten Rejang Lebong - Indriati Meilina Sari; Kiky Nurfitri Sari; Andika Prawanto; Selviana Anggraini; Paisal Ansiska (Universitas Galuh, 2026)
The transformation of agribusiness systems, which increasingly emphasizes value creation, sustainability, and cross-subsystem integration, has intensified attention toward local agricultural commodities and functional crops. Butterfly pea (Clitoria ternatea) is one such commodity developing within this context; however, studies in agricultural socio-economics and agribusiness related to this crop still exhibit conceptual fragmentation. This study aims to systematically synthesize the literature that examines butterfly pea from an agribusiness systems perspective, with a focus on value chain structures, institutional roles, and policy implications. This research employs a Systematic Literature Review (SLR) approach by searching the Scopus, Web of Science, and Google Scholar databases, as well as accredited national journals, covering publications from the past two decades. Articles meeting the inclusion criteria were analyzed using theory-informed thematic synthesis to identify patterns, mechanisms, and structural limitations within the literature. The synthesis results indicate that studies on butterfly pea remain dominated by micro-level and sectoral approaches, characterized by relatively short and localized value chains, unequal distribution of value added, and institutions that function primarily as technical facilitators. Public policy generally serves as an initial trigger for enterprise development but has not yet been systemically integrated to coordinate agribusiness subsystems. This study contributes conceptually by positioning butterfly pea within an integrated agribusiness systems framework, methodologically by organizing cross-study knowledge structures, and practically by providing implications for region-based agribusiness development, particularly in Rejang Lebong Regency.